Pelaksanaan Jaring Aspirasi Sebagai Komunikasi Publik Pemerintah Daerah Kabupaten Kulon Progo - Bawa Supratman; Fatah Nashir; Ahmad Syafii Rahman; Zainul Arifin; Cipto Sembodo (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2019)
Jaring Aspirasi is a liaison between the people and the local government leaders of Kulonprogo Regency. With the face-to-face model with a regent every Thursday, it is hoped that public information will be absorbed immediately to solve problems as soon as possible. This legal sociology study is intended to find out how the process works. then the research was conducted by means of observation, documentation and interviews. Triangulation was also carried out to obtain data validity as expected. Qualitative analysis is analytical descriptive of the results of the collected data. The information and public complaints in the seminar department are resolved in four categories depending on the quality of the information. This pattern satisfies members of the community and makes them realize that information cannot always be resolved at one time, especially in matters requiring disposition with other institutions. Kamispaginan as a form of public service is a form of joint deliberation between the regional government and the community which should be continued with increased socialization so that community participation will also increase.